Holocene Vegetation, Climate, and Carbon History on Western Kodiak Island, Alaska - Peteet, Dorothy M.; Nichols, Jonathan E.; Mann, Daniel H. (Frontiers in Earth Science, 2019)
A study of the Holocene history of Phalarope Pond, western Kodiak Island, Alaska is presented using lithology, LOI, pollen, macrofossils, AMS chronology, D/H ratios of peatland water, and carbon sequestration. The Holocene record begins atop a grey tephra, and spans from about 470 cm to the surface of the pond at 50 cm depth. Twelve AMS dates from identified macrofossils provide the chronology used to construct an age model. Early Holocene deposition (11,500 – 8700 ka) indicates a shallow pond at the site, with very low organic matter, abundant sedge and grasses nearby, Polypodiaceae ferns and Isoetes, a diverse moss assemblage including Sphagnum, and a high carbon accumulation rate. D/H ratios of peatland water are enriched. From 8700 – 3500 ka, low LOI, low accumulation rate, and very low carbon accumulation is represented until about 3500 years ago, with declines in ferns, sphagnum, sedges and grasses, and with increasing fungi and Isoetes. D/H ratios of peatland water become very depleted about 6000 ka. Neoglaciation is evident in the last 3500 years as increasing Artemisia, Betula, and Empetrum concurrent with Alnus decline indicate a cooler climate with increasing carbon accumulation.